Digital Transformation in Public and Non-Public Medical Diagnostic Entities in Poland: An Overview of Solutions - Gabig, Łukasz (Journal of Public Governance, 2024)
Objective: Digitisation and digitalisation are among the key developments in contemporary health care, including medical diagnostics, shaping the way diagnostic entities operate in both the public and private sectors. This article focuses on the theoretical analysis of digitisation processes in diagnostic units, with a particular focus on Information and Communications Technologies (ICTs) management and their impact on the efficiency of medical services.Research Design & Methods: The conducted analysis is based on a critical review of the literature on e-health, health IT management, and the digital transformation of medical diagnostics in the public and private sectors. Key areas of investigation include electronic medical records, telemedicine systems, artificial intelligence applications, and the Internet of Things within diagnostic facilities.Findings: The review indicates that implementing electronic medical records, telemedicine systems, artificial intelligence, and the Internet of Things significantly increases staff productivity and operational efficiencyin diagnostic facilities. At the same time, considerable challenges were identified, such as staff resistance to change, the need to ensure the interoperability of systems, and guaranteeing a high level of patient data security.Implications / Recommendations: The conclusions of the analysis highlight the key role of effective IT management and institutional support in fully exploiting the potential of digitisation and digitalisation. Suggestions forrecommendations for policymakers and health care managers were also formulated, targeting the strengthening of public–private partnerships (PPPs) as a strategic tool to support further digitisation of medical diagnostics.Contribution / Value Added: This work synthesises diverse strands of literature into a coherent theoretical framework for ICT management in medical diagnostics.JEL classification: I18, L86, O33, M15, L15, L33.